POGZ truncating alleles cause syndromic intellectual disability. Issue 1 (December 2016) - White, Janson; Beck, Christine; Harel, Tamar; Posey, Jennifer; Jhangiani, Shalini; Tang, Sha; Farwell, Kelly; Powis, Zöe; Mendelsohn, Nancy; Baker, Janice; Pollack, Lynda; Mason, Kati; et al.
Abstract Background Large-scale cohort-based whole exome sequencing of individuals with neurodevelopmental disorders (NDDs) has identified numerous novel candidate disease genes; however, detailed phenotypic information is often lacking in such studies. De novo mutations in pogo transposable element with zinc finger domain (POGZ ) have been identified in six independent and diverse cohorts of individuals with NDDs ranging from autism spectrum disorder to developmental delay. Methods Whole exome sequencing was performed on five unrelated individuals. Sanger sequencing was used to validate variants and segregate mutations with the phenotype in available family members. Results We identified heterozygous truncating mutations inPOGZ in five unrelated individuals, which were confirmed to be de novo or not present in available parental samples. Careful review of the phenotypes revealed shared features that included developmental delay, intellectual disability, hypotonia, behavioral abnormalities, and similar facial characteristics. Variable features included short stature, microcephaly, strabismus and hearing loss. Conclusions WhilePOGZ has been associated with neurodevelopmental disorders in large cohort studies, our data suggest that loss of function variants inPOGZ lead to an identifiable syndrome of NDD with specific phenotypic traits. This study exemplifies the era of human reverse clinical genomics ushered in by large disease-directed cohort studies; first defining a new syndrome molecularly and, only subsequently, phenotypically.